2020
DOI: 10.1109/ojemb.2020.2965084
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Three-Dimensional Scaffolds Modulating Fate of Breast Cancer Cells Using Stiffness and Morphology Related Cell Adhesion

Abstract: Artificially engineering the tumor microenvironment in vitro as a vital tool for understanding the mechanism of tumor progression. In this study, we developed three-dimensional cell scaffold systems with different topographical features and mechanical properties but similar surface chemistry. The cell behavior was modulated by the topography and mechanical properties of the scaffold. Adenocarcinoma (MCF7), triple-negative (MDA-MB-231) and premalignant (MCF10AneoT) breast cancer cells were seeded on the scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The results of GO analysis then indicated that PAMR1-related genes were mainly enriched in the regulation of extracellular matrix organization, cell adhesion, and blood vessel development. These functions are closely associated with cancer; loss of cellular adhesion is a crucial step in tumor metastasis, whereas blood vessel development contributes to both tumor growth and spread 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of GO analysis then indicated that PAMR1-related genes were mainly enriched in the regulation of extracellular matrix organization, cell adhesion, and blood vessel development. These functions are closely associated with cancer; loss of cellular adhesion is a crucial step in tumor metastasis, whereas blood vessel development contributes to both tumor growth and spread 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors determined that the geometry of PO250+ (fine checkerboard), with a pore size of 250 μm, was optimal towards eliciting strong cell proliferation and viability, as well as causing the expression of the liver-specific mRNA CYP3A4 and protein albumin [ 223 ]. With specific reference to the cellular behavior of cancer cells, Hanumantharao et al carried out an interesting study examining how different topographical features and mechanical properties of PCL scaffolds influenced human ER+ and triple negative breast cancer cells [ 227 ]. The authors found that human MCF-7 ER+ breast cancer cells proliferated well on a variety of different scaffold topographies, where the MCF-7 cells had a higher rate of proliferation on scaffolds with low Young’s modulus and stiffness.…”
Section: Conclusion and Future Explorationmentioning
confidence: 99%
“…The authors found that human MCF-7 ER+ breast cancer cells proliferated well on a variety of different scaffold topographies, where the MCF-7 cells had a higher rate of proliferation on scaffolds with low Young’s modulus and stiffness. On the other hand, human MDA-MB-231 triple negative breast cancer cells preferred scaffolds that had a high matrix stiffness [ 227 ]. These results suggest that cancer cells respond to changes in scaffold stiffness, mechanical properties, and topography, which should be considered when developing a 3D bioprinted scaffold to model the tumor microenvironment.…”
Section: Conclusion and Future Explorationmentioning
confidence: 99%
“…Different types of BCCs respond differently to various levels of matrix stiffness. Triple-negative BCCs favor honeycomb geometries with greater stiffness, adenocarcinoma MCF-7 cells prefer mesh scaffolds with low elastic modulus, and pre-malignant cells favor aligned scaffolds with high stiffness and contact guidance ( 22 ). Additionally, it has been reported that rigidity sensing by healthy mammary cells is impaired in BCCs but remains active in normal mammary cells ( 23 ).…”
Section: Role Of the Physical Microenvironment As A Driver Of Bone Metastasismentioning
confidence: 99%